The burden of firearm injuries at two district level emergency centres in Cape Town, South Africa: a descriptive analysis - Bush, Luke Anthony (Division of General Surgery, 2022)
Introduction Firearm injuries account for an increasingly significant portion of violence related trauma experienced in South Africa. The related burden on district level emergency care, surgical and inpatient services is poorly described. This research aims to provide epidemiological and health service data on patients sustaining firearm injuries presenting at Mitchells Plain Hospital and Heideveld Emergency Centre. The research also assesses the association of the Triage Early Warning Score with anatomical location of injury, the need for surgical intervention and mortality. A geographical analysis of incident location with respect to home address has also been undertaken. Methods All patients who presented to these emergency centres with a firearm injury over a 12-month period (1 Jan 2019 – 31 Dec 2019) were eligible for inclusion in a retrospective chart review. Results Seven-hundred-and-seventy-six firearm injuries were analysed with those injured having a mean age of 27 years and 91% of those injured being male. Sixty-seven percent of patients self-presented and there were 18 deaths in the emergency centre and a further 23 as an inpatient. The Triage Early Warning Score and Shock Index both showed statistical significance when comparing those not surviving to hospital discharge against those that did survive (p<0.01). Discussion Firearm injuries represented 5.7% of all trauma seen at these two facilities and likely form a higher proportion of the injury profile than at other district services in the City of Cape Town. Although a significant number of those injured are transferred out to tertiary centres that are better capacitated to manage these injuries, many remain at district level for their care. Conclusion Firearm injuries, the immediate surgical needs of those injured and the long-term consequence of those injuries pose a significant burden on limited healthcare resources. Multi-sectoral action, supported by evidence-based primary and secondary preventative strategies, is required to reduce this intentional injury burden, and mitigate the effects.